Penggunaan Bahasa Isyarat SIBI dan BISINDO untuk Siswa Tuli di Sekolah Luar Biasa Negeri Pembina Medan - Meysa Malika; Berlianti Berlianti (Concept: Journal of Social Humanities and Education, 2025)
Sign language is the primary form of communication for deaf individuals to convey ideas, thoughts, and receive information from others.